Intergenerational social mobility, smoking and smokeless tobacco (snus) use among adolescents during 2008–2017. (November 2019) - Ruokolainen, Otto; Ollila, Hanna; Lahti, Jouni; Rahkonen, Ossi
Abstract: Background: Socioeconomic differences in smoking and other tobacco use are prevalent in adolescents. Less is known about the association between intergenerational social mobility and tobacco use. Methods: Five waves of national cross-sectional School Health Promotion Study during 2008–2017 in Finland were used, including non-academically and academically oriented adolescents (15–21 years, N = 384, 379). The adolescents' educational orientation was compared with the educational track of the parents as a proxy for intergenerational social mobility, which was used as the independent variable in regression models to examine the differences in daily smoking and daily snus use. Results: Smoking declined in all mobility groups over time, but remained more prevalent among non-academically oriented adolescents among boys and girls. Daily snus use among boys increased over time in all mobility groups. Multiple adjusted models showed that upward mobility and downward mobility are differently associated with tobacco use, the latter increasing the probability of tobacco use compared with the stable high group (boys: smoking: OR = 5.24, 95% CI 5.02–5.46; snus use: OR = 1.57, 95% CI 1.50–1.66). In smoking, absolute socioeconomic differences between the mobility groups decreased over time while relative differences increased. In snus use, both absolute and relative differences increased. Conclusions: Adolescent smoking and snus use associate strongly with the adolescent's educational track, irrespective of the social mobility class. Non-academically oriented adolescents have an increased risk of tobacco use. The academic and non-academic orientation should already be taken into account in tobacco use prevention in basic education. Highlights: Youth smoking and snus use are strongly associated with the educational track. The risk for tobacco use is elevated in downward-mobile and stable low adolescents. Absolute differences in smoking decreased while relative differences increased. Absolute and relative differences in snus use increased among boys.